Alternative Measurement of Vertical Dimension of Occlusion with Apikal Software - Kusoemo, Andre; Siahay, Andres Jordan; Habar, Ike Damayanti; Dammar, Irfan (Indonesia Prosthodontic Association, 2021)
Object: To find out the VDO measurement with digital photo analysis method using Apikal analysis software, which help to measure VDO directly based on patient’s photograph. Methods: The samples are 15 patients, with condition of missing all teeth in the upper and lower jaws for at least 6 (six) months. Then measurements of vertical dimension of occlusion were made using Apikal digital analysis software and the Two Dots technique as comparison. Results: Using the Kruskal Wallis test to compare the measurement of the vertical dimension of the occlusion with the Two Dots technique and Apikal software, there is no difference between the direct and indirect (digital analysis) on vertical dimension of occlusion measurements. An insignificant difference found, and the same result occur between both, with p value 0.05 (0.816*). Conclusion: There is no difference of results on measuring the vertical dimension of occlusion between the Two Dots and Apikal analysis software, and there is a significant relationship between measurements on the face using the Two Dots technique and Apikal software. Apikal analysis software can help determine and as alternative method to do the measurement of vertical dimension of occlusion in patient indirectly